A novel soft reliability-based iterative majority-logic decoding algorithm with uniform quantization - 袁建国 汪哲 何昌伟 林金朝 庞宇 (Optoelectronics letters, 2017)
In this paper, a novel soft reliability-based iterative majority-logic decoding algorithm with uniform quantization is proposed for regularly structured low density parity-check（LDPC） codes. A weighted measure is introduced for each check-sum of the parity-check matrix and a scaling factor is used to weaken the overestimation of extrinsic information. Furthermore, the updating process of the reliability measure takes advantage of turbo-like iterative decoding strategy. The main computational complexity of the proposed algorithm only includes logical and integer operations with the bit uniform quantization criterion. Simulation results show that the novel decoding algorithm can achieve excellent error-correction performance and a fast decoding convergence speed.